Anatole - Titus, Eve; Galdone, Paul. (New York Dragonfly Books, 2006)
A French mouse decides to earn an honest living by tasting the cheese in a cheese factory and leaving notes about its quality.
The 50th anniversary of a classic
Ages 5-9.
Caldecott Medal Honor Book, 1957.
Keywords: Mice -- Fiction; Cheese -- Fiction; France -- Fiction